PERAN POLIMORFISME GEN INTERFERON-g (IFNG) PADA FENOTIP HISTOLOGI NEFRITIS LUPUS - Kusworini Handono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2010)
Lupus Nephritis (LN) is a serious complication of Systemic Lupus Erythematosus (SLE) with the development of end stage renaldisease in 10–70% patients within 5 years. The condition is classified into 6 different classes according WHO criteria. Several studiesshowed that there were significant clinical manifestation differences between class III, IV and class V LN. It has been suggested that theclass differences of LN was related to the cytokines balance and genetic factor. The objective of this study was to determine the role ofg-Interferron gene (IFNG) polymorphism in the class differences of LN. The study was conducted in 40 female SLE patients at the Dr.Saiful Anwar Hospital, Malang. Histologic phenotypes classification was based on World Health Organization (WHO) criteria (1995).Microsatelite polymorphism within the first intron of the IFNg gene on chromosome 12q24.1 was performed by DNA sequencing. Theallele difference between LN classes and healthy controle were analysed by Chi-square, the risk of LN in patients with certain IFNG allelewas calculated using Odds Ratio. The result showed that the frequency of IFNG 112 allele were higher in SLE patients compared withhealthy controls (succeptible allele) and the risk to have class V LN in patients with IFNG 112 was 6 times higher compared with patientswithout these allele. There is an association between IFNG polymorphism with the LN classes.